EXPERIENCE OF ORGANIZATION OF INDIVIDUAL DOSIMETRIC CONTROL OF THE STAFF IN THE PERM KRAI - V. N. Bezgodov; I. A. Shilov (Радиационная гигиена, 2015)
The article summarizes many years of experience of individual dosimetric control of the enterprise personnel working with the ionizing irradiation sources in the Perm Krai.